Adulterants survey in informal raw milk and uat milk sold in a county in south (Research, Society and Development, 2022)
Milk is composed of a mix of complex substances and constitutes one of the main foods consumed in the world, due to its organoleptic and nutritional characteristics. The lack of quality of this product is related to various forms of fraud, causing food and public health problems. This research aimed to detect the presence of adulterants in “informal” raw milk and UHT milk sold in a municipality in the south of Tocantins. Six samples of UHT milk and three samples of informal raw milk were collected, which were submitted to sensory analysis, alizarol, formaldehyde, chlorine, hypochlorite, sucrose, chloride, sodium hydroxide tests and pH determination. An unsatisfactory result was detected in only one UHT milk sample (LT3), which showed the presence of hypochlorite. In the analysis of informal raw milk, two samples were detected with alterations in one of the analyzed parameters: the LC1 sample showed changes in its organoleptic characteristics and the LC2 sample showed a positive result in the chloride test. The other analyzes of adulterants and physical-chemical characteristics were found in accordance with the criteria defined in legislation. This research shows the need for monitoring and inspection of the quality parameters of products on the market, especially the need for greater control over illegally traded milk, which is more subject to the presence of adulterants.